Examining the Role of Attentional Bias in the Context of Negative and Positive Content in Real-World and Laboratory- Based Settings - Szeremeta, Elise Maree (Curtin University, 2022)
This thesis investigates patterns of biased attention in the context of both negative and positive information, and related effects on emotional and behavioural processes. These processes were examined in the context of contamination fear and mitigation behaviour related to the COVID-19 pandemic, and also the neural underpinnings of attention and emotion using non-invasive neurostimulation of the prefrontal cortex.